Same-sex role model effects in education - Alexandra de Gendre; Jan Feld; Nicolás Salamanca; Ulf Zölitz (University of Zurich, Department of Economics, 2023)
We study same-sex role model effects of teachers with a meta-analysis and our own study of three million students in 90 countries. Both approaches show that role model effects on performance are, on average, small: 0.030 SD in the meta-analysis and 0.015 SD in our multi-country study. Going beyond test scores, our multicountry study documents larger average role model effects on job preferences (0.063 SD). To understand the universality of these effects, we estimate the distributions of country-level same-sex role model effects. Although role model effects on test scores appear universally small, we find substantial cross-country variation for job preferences, with larger effects in countries with larger gender gaps. These results are consistent with role models inspiring students to overcome gender stereotypes and pursue a STEM career. However, in countries with negligible gender gaps, role models do not seem to have this equalizing function.
Keywords: I21; I24; J24; 330; Same-sex role models; STEM; teachers; external validity; multi-country study; gender role models; standardized test scores; grades; job preferences; science; math; reading; meta-analysis; meta-science